2018
DOI: 10.3390/ma11020212
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Glass-Ceramics Produced by Sol-Gel: A Suitable Alternative for Photonic Materials

Abstract: Transparent glass-ceramics have shown interesting optical properties for several photonic applications. In particular, compositions based on oxide glass matrices with fluoride crystals embedded inside, known as oxyfluoride glass-ceramics, have gained increasing interest in the last few decades. Melt-quenching is still the most used method to prepare these materials but sol-gel has been indicated as a suitable alternative. Many papers have been published since the end of the 1990s, when these materials were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 115 publications
(140 reference statements)
1
30
0
Order By: Relevance
“…As was presented in Figure 5, the emission spectrum of CaF 2 :Eu 3+ GCs also consisted of the characteristic bands of Eu 3+ ions corresponding to the intra-configurational 5 The photoluminescence decay curve of the 5 D0 state of Eu 3+ ions recorded for fabricated glassceramics was presented in the inset of Figure 5. The decay curve was well-fitted to double-exponential function and therefore, it was distinguished two different decay components: fast (τ1 = 1.63 ms) and slow (τ2 = 12.84 ms).…”
Section: Luminescence Behavior Of Fabricated Sol-gel Materialsmentioning
confidence: 79%
See 1 more Smart Citation
“…As was presented in Figure 5, the emission spectrum of CaF 2 :Eu 3+ GCs also consisted of the characteristic bands of Eu 3+ ions corresponding to the intra-configurational 5 The photoluminescence decay curve of the 5 D0 state of Eu 3+ ions recorded for fabricated glassceramics was presented in the inset of Figure 5. The decay curve was well-fitted to double-exponential function and therefore, it was distinguished two different decay components: fast (τ1 = 1.63 ms) and slow (τ2 = 12.84 ms).…”
Section: Luminescence Behavior Of Fabricated Sol-gel Materialsmentioning
confidence: 79%
“…Transparent glass-ceramics (GCs) containing fluoride nanocrystals fabricated using high-temperature melt-quenching or low-temperature sol-gel method are suitable modern materials for lasers, optical waveguides, solid-state lighting and numerous photonic applications [1][2][3][4][5]. Depending on chemical composition and technological conditions, nano-or micro-crystals are usually well-formed during temperature-controlled crystallization of precursor glasses or xerogels.…”
Section: Introductionmentioning
confidence: 99%
“…The nanostructure of the PCGs can be obtained using transmission electron microscopy (TEM) and its high-resolution analogue (HRTEM), as it is demonstrated in [105][106][107][108]. In particular, HRTEM can be used to reveal the lattice planes and the crystal-size distribution.…”
Section: Characterization Of Pcgsmentioning
confidence: 99%
“…Since then, there has been much interest in developing novel transparent oxyfluoride glass-ceramics containing REE-doped fluoride crystals. Reviews on transparent oxyfluoride GCs in bulk form can be found in [163] and [108]. Some of the first transparent oxyfluoride GC fibers were with the composition of 48SiO 2 -11Al 2 O 3 -7Na 2 CO 3 -10CaO-10PbO-11PbF 2 -3ErF 3 and 48SiO 2 -11Al 2 O 3 -7Na 2 CO 3 -10CaO-10PbO-10PbF 2 -3YbF 3 -1ErF 3 [105].…”
Section: Glass-ceramics Fibersmentioning
confidence: 99%
“…Another great advantage of GCs with respect to other kinds of materials is related with the availability of different processing methods: from classical melt‐quenching (MQ) to sol‐gel (SG), that allows the preparation of materials as bulk, films, powder or fibers. Most works published up to date about oxyfluoride GCs concern bulk materials prepared MQ doped with RE ions, however, a review paper about SG oxyfluoride GCs was also published recently . Recently, the preparation of optical fibers with GC core has emerged as interesting field and several works have been published since 2015.…”
Section: Introductionmentioning
confidence: 96%